Side Effects of Anticonvulsant Monotherapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The severity and nature of side effects and doses and plasma levels of phenobarbital (PB), primidone (PRM), phenytoin (PHT), carbamazepine (CBZ), and valproate (VPA) were examined in 392 pediatric outpatients at the Division of Paediatric Neurology, National Hospital "Marques de Valdecilla", University of Cantabria, Santander, Spain.